G-quadruplex augments translation in the 5 ` untranslated region of transforming growth factor beta 2 - Agarwala, Prachi; Pandey, Satyaprakash; Mapa, Koyeli; Maiti, Souvik (Biochemistry, 2013)
Transforming growth factor beta 2 (TGF beta 2) is a versatile cytokine with a prominent role in cell migration, invasion, cellular development, and immunomodulation. TGF beta 2 promotes the malignancy of tumors by inducing epithelial-mesenchymal transition, angiogenesis, and immunosuppression. As it is well-documented that nucleic acid secondary structure can regulate gene expression, we assessed whether any secondary motif regulates its expression at the post-transcriptional level. Bioinformatics analysis predicts an existence of a 23-nucleotide putative G-quadruplex sequence (PG4) in the 5' untranslated region (UTR) of TGF beta 2 mRNA. The ability of this stretch of sequence to form a highly stable, intramolecular parallel quadruplex was demonstrated using ultraviolet and circular dichroism spectroscopy. Footprinting studies further validated its existence in the presence of a neighboring nucleotide sequence. Following structural characterization, we evaluated the biological relevance of this secondary motif using a dual luciferase assay. Although PG4 inhibits the expression of the reporter gene, its presence in the context of the entire 5' UTR sequence interestingly enhances gene expression. Mutation or removal of the G-quadruplex sequence from the 5' UTR of the gene diminished the level of expression of this gene at the translational level. Thus, here we highlight an activating role of the G-quadruplex in modulating gene expression of TGF beta 2 at the translational level and its potential to be used as a target for the development of therapeutics against cancer.

G-Quadruplexes as tools for synthetic biology - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Chembiochem, 2013)
With the potential to engineer biological systems, synthetic biology is an emerging field that combines various disciplines of sciences. It encompasses combinations of DNA, RNA and protein modules for constructing desired systems and the rewiring of existing signalling networks. Despite recent advances, this field still lags behind in the artificial reconstruction of cellular processes, and thus demands new modules and switches to create genetic circuits. The widely characterised noncanonical nucleic acid secondary structures, G-quadruplexes are promising candidates to be used as biological modules in synthetic biology. Structural plasticity and functional versatility are significant G-quadruplex traits for its integration into a biological system and for diverse applications in synthetic circuits.
Keywords: G-quadruplexes; ribozymes; synthetic biology; topology; zipcodes